6.12 THE ESSENCE OF BERDAK’S WORKS, A MANIFESTATION OF KARAKALPAK LITERATURE - Aliboyeva Dilrabo Dilshod qizi Yo’lchibayeva Shaxlo Bekzod qizi Toshkent pediatriya tibbiyot instituti tibbiy pedagogika va davolash fakulteti (Innovative technologies in construction Scientific Journal, 2024)
In this article, Berdak,who has become the pride of Karakalpak, covers his difficulties in life and the meaning of his poems. Keywords: person, nation, Berdak, poet, difficult, material, feudal, Muslim. INTRODUCTION. When a person is born, he learns, gets used to it and searches. I think that no one should pass this world without learning something. As our first president said, "Material and spiritual life are like two wings of a bird". Without material wealth,it is impossible to reach the peak of spirituality will not go far. And to arm ourselves with masterpieces of philosophical vision, we can make shields only from books.